Mobile Phone Use “on the Road”: A Self-Report Study on Young Drivers - Fraschetti, Angelo; Cordellieri, Pierluigi; Lausi, Giulia; Mari, Emanuela; Paoli, Elena; Burrai, Jessica; Quaglieri, Alessandro; Baldi, Michela; Pizzo, Alessandra; Giannini, Anna Maria (Frontiers in Psychology, 2021)
Background. Extensive research has shown that multitasking has a negative influence on driving performance; multitasking activities can range from conversations and telephone messages to listening to music. Distraction due to cell phone use while driving is one of the main causes of traffic accidents, particularly among young drivers. Objective. The main purpose of this study was to investigate whether some variables (e.g. Sensation-Seeking, preferences of Multi-tasking) could affect cell phone use while driving in young drivers. Secondly, we evaluated the gender difference in driver distraction. Setting and participants. The sample consists of 424 Italian students (56% males) with a mean age of M =18.38 and SD =1.029 [age 18-21]. A Self-report questionnaire was specifically prepared to assess variables such as: Attitude toward Multitasking, Perceived self-efficacy in Multitasking, Accident Risk perception, General Multitasking Habits, and Sensation Seeking. Results. Through SEM modeling, we found the attitude to distraction while driving to be largely explained by the variables that have been considered. Using multigroup analysis (MGSEM), the model we developed appears to be suitable for explaining the behaviors of both young male and female drivers. Furthermore, data comparison showed that females were more prone to Risk perception towards multitasking, and Risk perception when using a mobile phone while driving. Males have obtained higher mean scores in Sensation Seeking, Perceived Self-Efficacy in Multitasking, and Cell phone use while Driving. Conclusion. Our research has shown the influence of some variables on subjects prone to multitasking while driving. Furthermore, we discussed the importance of considering these variables in the implementation of effective road safety education projects on driving distraction.